2015
DOI: 10.1016/j.ridd.2014.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Association between pupillary light reflex and sensory behaviors in children with autism spectrum disorders

Abstract: Atypical pupillary light reflexes (PLR) has been observed in children with autism spectrum disorders (ASD), which suggests potential autonomic nervous system (ANS) dysfunction in ASD. ANS is also involved in modulating sensory processing and sensory dysfunction has been widely reported in children with ASD. However, the potential association between physiological measurements of PLR and behavioral observations (e.g. sensory behaviors) has not been examined extensively in literature. In this study, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 28 publications
3
47
0
1
Order By: Relevance
“…This notion corresponds to the finding that the presence of extensive white matter lesions in children with severe cerebral palsy was associated with poorer language comprehension (24). Our ideas also match those of Fan et al and Daluwatte et al, who suggested that white matter abnormalities or disturbed modulation of sensory input might have explained slow pupillary responses in the children autism spectrum disorder that they studied (17,25). Additional studies, for example with the use of diffusion tensor imaging, are needed to test this hypothesis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This notion corresponds to the finding that the presence of extensive white matter lesions in children with severe cerebral palsy was associated with poorer language comprehension (24). Our ideas also match those of Fan et al and Daluwatte et al, who suggested that white matter abnormalities or disturbed modulation of sensory input might have explained slow pupillary responses in the children autism spectrum disorder that they studied (17,25). Additional studies, for example with the use of diffusion tensor imaging, are needed to test this hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…Our ideas also match those of Fan et al. and Daluwatte et al., who suggested that white matter abnormalities or disturbed modulation of sensory input might have explained slow pupillary responses in the children autism spectrum disorder that they studied . Additional studies, for example with the use of diffusion tensor imaging, are needed to test this hypothesis.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, Casanova et al [ 105 ] saw a significant increase in cardiac vagal control in autistic subjects treated with low-frequency (LF) repetitive transcranial magnetic stimulation (rTMS). Daluwatte et al [ 106 ] demonstrated constricted pupillary light reflexes (PLR) in ASD subjects, suggesting a lowered parasympathetic modulation during sensory stimulation. It should also be mentioned that heavy metal exposures may exacerbate parasympathetic dominant states [ 107 , 108 ]; interestingly, it may be the case that levels of these heavy metals may be elevated in ASD subjects out of a consequence of this heightened parasympathetic state induced in utero.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that questionnaire measures and behavioral ratings are at best a weak indicator of autonomic activity and highlight the importance of including multiple measures to examine sensory processing in ASD. In a study of 5–19 year olds looking at ANS function in ASD and its relation to sensory symptoms, Daluwatte et al ( 2015 ) found that lower pupil constriction amplitude, a measure associated with parasympathetic activity, was related to increased overall sensory symptoms in ASD. The authors conclude that certain atypical sensory symptoms in ASD seem to be related to reduced parasympathetic modulation.…”
Section: Sensory Symptoms In Asdmentioning
confidence: 99%